Pengaruh Kemudahan Penggunaan Aplikasi Access by KAI Terhadap Effort Expectacy dengan Customer Trust Sebagai Mediasi dalam Perspektif Bisnis Islam: Studi Pengguna Aplikasi Access by KAI pada Pelanggan PT Kereta Api Persero di Stasiun Tanjung Karang - Cyndi Eka Pratiwi; Yulistia Devi; Citra Etika (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to analyze the effect of ease of use of the Access By KAI application on effort expectancy, with customer trust as a mediator from an Islamic business perspective among Access By KAI application users at Tanjung Karang Station. This study used a quantitative method by distributing questionnaires to 96 respondents. Data analysis was performed using SmartPLS 4.0. The results showed that ease of use had a positive and significant effect on customer trust, and customer trust had a positive and significant effect on effort expectancy. Customer trust significantly mediated the relationship between ease of use and effort expectancy. This finding indicates that ease of use is sufficient to reduce effort expectancy. From an Islamic business perspective, these results emphasize the importance of ease of service, reflecting the principle of taysir (making things easier for others) and providing the best service, in line with the value of amanah (trustworthiness) in service and transactions. Future research is recommended to add variables such as perceived usefulness, quality and completeness of features, or service to broaden understanding of the factors influencing business expectations.